Necessity accordance of baptism like a challenge for evangelization of his parents - JANCZEWSKI, ZBIGNIEW (Prawo Kanoniczne, 2016)
Canon 868 paragraph 1 number 2 decides: for an infant to be baptised lawfully it is required: that there be a well-founded hope that the child will be brought up in the catholic religion. If such hope is truly lacking, the baptism is, in accordance with the provisions of particular law. In Poland many Catholics who life is discordant with hope want to baptise his children.